The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1121/1.4869256
|View full text |Cite
|
Sign up to set email alerts
|

Refining a model of hearing impairment using speech psychophysics

Abstract: The premise of this study is that models of hearing, in general, and of individual hearing impairment, in particular, can be improved by using speech test results as an integral part of the modeling process. A conceptual iterative procedure is presented which, for an individual, considers measures of sensitivity, cochlear compression, and phonetic confusions using the Diagnostic Rhyme Test (DRT) framework. The suggested approach is exemplified by presenting data from three hearing-impaired listeners and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…An important extension of the model would be to include aspects of hearing impairment, such as elevated audiometric thresholds, reduced frequency selectivity, loss of compression and other supra-threshold deficits (cf. J€ urgens et al, 2014;Jepsen et al, 2014). The results of the present study suggest that, if a version of the model that can account for consonant perception in unaided HI listeners was established, the effects of hearing-instrument compensation strategies might be well-represented in the model predictions.…”
Section: Perspectivessupporting
confidence: 54%
See 1 more Smart Citation
“…An important extension of the model would be to include aspects of hearing impairment, such as elevated audiometric thresholds, reduced frequency selectivity, loss of compression and other supra-threshold deficits (cf. J€ urgens et al, 2014;Jepsen et al, 2014). The results of the present study suggest that, if a version of the model that can account for consonant perception in unaided HI listeners was established, the effects of hearing-instrument compensation strategies might be well-represented in the model predictions.…”
Section: Perspectivessupporting
confidence: 54%
“…If such a model can account for the effects of specific HA/CI processing strategies on consonant perception, it may provide useful information about the auditory cues that contribute to the recognition of a specific consonant or its confusion with another consonant. Several approaches for modeling consonant perception in NH listeners (Cooke, 2006;J€ urgens and Brand, 2009) and in HI listeners (Holube and Kollmeier, 1996;J€ urgens et al, 2014;Jepsen et al, 2014) have been proposed. While the mentioned models were shown to account for consonant recognition scores in masking noise (or in quiet at low signal levels), they did not account well for the consonant confusions, i.e., the predicted errors were different from the listeners' errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of these proposals, the applied auditory model is not sufficiently detailed to provide adequate options for implementing realistic hearing deficits. In the last decades, auditory models have been developed which are more sophisticated and meanwhile can simulate hearing deficits [12][13][14][15]. In [16,17], it is shown that…”
Section: Introductionmentioning
confidence: 99%